Geriatric Assessment as a qualification element for elective and emergency cholecystectomy in older patients. Issue 1 (December 2016) - Kenig, Jakub; Wałęga, Piotr; Olszewska, Urszula; Konturek, Aleksander; Nowak, Wojciech
Abstract Background Older patients experience a higher incidence of postoperative complications after cholecystectomy compared with younger patients. However, most studies have not considered patient frailty, particularly regarding emergency cholecystectomy. The aim of this prospective study was to evaluate outcomes in frail older patients eligible for elective and emergency cholecystectomy. Methods Preoperative Geriatric Assessment (GA) was performed in consecutive patients aged 65+ years, operated for biliary disease. The GA evaluated the functional, cognitive, comorbidity, depressive, nutritional, and polypharmacy status and patients with two or more abnormal domains were considered frail. Outcomes of interest were 30-day postoperative mortality, morbidity, and length of hospital stay (LOS). Results A total of 126 patients (median age 74; range 65–93 years) were included. There was no difference between elective frail and non-frail patients regarding postoperative mortality (0 %) and morbidity (6 % vs. 5 %;p  = 0.76). LOS was not significantly longer in the frail group (5.6 vs. 4 days;p  = 0.22). In the emergency-admitted patients, almost all complications occurred in the frail population (mortality 5 % vs. 0 %; morbidity 36.7 % vs. 3.3 %, compared with non-frail patients, respectively;p  < 0.01) and LOS was significantly longer (10.3 (frail) vs. 6 days (non-frail);p  = 0.03). Frail status was a significant independent predictive factor for postoperative complications in the emergency population, only (odds ratio: 3.4 (1.2–9.7);p  = 0.02). Conclusions Elective laparoscopic cholecystectomy is a safe and effective surgical technique also for older frail patients. In emergency settings, frail patients have significantly more complications and a longer LOS. However, the role of severity of frailty and the most reliable GA tools require further study. Trial registration ISRCTN14976998 (retrospectively registered)